2019
DOI: 10.1186/s13102-019-0147-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low level laser irradiation on oxidative stress, muscle damage and function following neuromuscular electrical stimulation. A double blind, randomised, crossover trial

Abstract: BackgroundLow level laser therapy (LLLT) is among novel methods for preventing and treating muscle damage and soreness induced by volitional exercise, but little is known about using LLLT before neuromuscular electrical stimulation. The aim of this first randomised, double blind, crossover trial addressing this issue was to evaluate effects of LLLT on muscle damage and oxidative stress, as well as recovery of muscle function after a single session of isometric neuromuscular electrical stimulation(NMES).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
0
29
0
1
Order By: Relevance
“…Currently, vast quantities of empirical evidence have indicated that oxidative stress and inflammation may account for the altered regulatory pathways in myopia and that oxidative damage associated with hypoxic myopia can alter the neuromodulation of nitric oxide and dopamine during eye growth [ 4 , 5 ]. Analyzing the possible mechanisms of the inhibitory effects of LLLT treatment on myopia could help to protect patients from the effects of oxidative stress and decrease inflammation that accompanies myopia [ 27 ]. LLLT has maximal effects on the nitric oxide system and decreases the severity of oxidative stress in both animal studies [ 28 ] and clinical studies [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, vast quantities of empirical evidence have indicated that oxidative stress and inflammation may account for the altered regulatory pathways in myopia and that oxidative damage associated with hypoxic myopia can alter the neuromodulation of nitric oxide and dopamine during eye growth [ 4 , 5 ]. Analyzing the possible mechanisms of the inhibitory effects of LLLT treatment on myopia could help to protect patients from the effects of oxidative stress and decrease inflammation that accompanies myopia [ 27 ]. LLLT has maximal effects on the nitric oxide system and decreases the severity of oxidative stress in both animal studies [ 28 ] and clinical studies [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five to six weeks of green tea consumption increased the athlete’s antioxidant capacity, which in turn increased the level of total antioxidants in plasma during and after an intense running exercise session as well as prevented or inhibited excessive lipid peroxidation caused by the exercise. Several studies have shown that green tea has a protective effect (i.e., increased plasma antioxidant and decreased plasma lipid hydroperoxide levels) against oxidative stress produced during and after exercise [ 58 , 59 ]. In addition, green tea consumption inhibits or reduces plasma creatine kinase and xanthine oxidase activities after exercise.…”
Section: Green Tea and Prevention Of Oxidative Stress Production During Exercisementioning
confidence: 99%
“…Strategies, such as consuming food (nutrients) with antioxidant and anti-inflammatory effects [ 11 , 12 ], low-level laser therapy [ 13 ], and cold water immersion [ 14 ] treatment, have been suggested to reduce the inflammatory response and excessive OS generation from acute exercise, and help exercise-induced damaged muscles recover faster. The strategies remain controversial, but some of them were proven to be effective.…”
Section: Introductionmentioning
confidence: 99%